A zona cultural da Praça da Estação: um estudo sobre seu processo de transformação sob a ótica da Economia Criativa - Carvalho, Daniel de Miranda (2021)
This paper analyzes the process of creation and flourishing of the Praça da Estação Cultural Zone, understood as a cultural and creative district in Belo Horizonte (MG). The main objective is to identify the relationships between the agents and understand the factors that interacted to make the most expressive cultural space in the capital of Minas viable. The study is theoretically based on ideas about how the artistic class initiates a process of transformation of the creative city described by Elsa Vivant (2012), from the perspective of the existing combination between hard and soft infrastructure in the creation of a “third space”, according to Landry (2008), on the understanding of the process of organization and emergence of “Natural” Cultural Districts, by Ster and Seifert (2007), and on the theories of Michael Storper (2013) about the elements present in the “winning regions”. In methodological terms, it is an exploratory research with a qualitative approach carried out through bibliographical and documentary research, in addition to a field study consisting of interviews with social actors directly involved in the constitution of the Cultural Zone. In the transformation process, which includes investment in hard infrastructure, as well as the renovation of Praça da Estação and the creation of the Museu de Artes e Ofícios, the importance of the role of civil society and academia that assume the role of artists off - described by (VIVANT, 2012) and the presence of the elements established by Storper (2013): innovation, institutions and policy. Finally, this dissertation summarizes the set of researches about the formation of territories, districts and creative spaces, whose applicability can be thought of in terms of contribution to public policies for the development and/or strengthening of creative territories